Pola Sidik Jari Anak-anak Sindrom Down di SLB Bakhti Kencana dan Anak Normal di SD Budi Mulia Dua Yogyakarta - Ainur, Annisa; Hastuti, Janatin; Nugraha, Zainuri Sabta (Faculty of Medicine, Universitas Islam Indonesia, 2009)
Dermatoglyphics is not only used to identify criminal, but also useful in clinical field. There are some evidence that people with chromosome abnormalities like Down Syndrome (trisomy 21), have abnormality in dermatoglyphics pattern compared to normal people. It can be used to help confirming the diagnose. The goals are to study the variation and distribution difference of dermatoglyphics and also the difference of Total Ridge Count (TRC) on children with Down Syndrome at SLB Bakhti Kencana and normal children at SD Budi Mulia Dua Yogyakarta. This research use cross sectional study with 2 groups of subject that consist of 10 person. The dermatoglyphics was taken by sticking both hands that had been marked with purple ink on the paper. Gathered data was analyzed with descriptive analysis and statistic analysis using Chi Square test, Fisher test and independent sample T-test with SPSS 14 for windows. The results show that the highest mean percentage of dermatoglyphics on Down Syndrome children is whorl (55%), on the otherhand the highest mean percentage of dermatoglyphics on normal children is loop ulna (53%). There is significant difference (pKeyword : dermatoglyphics, Down Syndrome, normal children